Lingual Artery Bifurcation Aneurysms for Training and Evaluation of Neurovascular Devices - Raymond, Jean (AJNR Am J Neuroradiol, 2004)
Summary: We present a canine lingual artery bifurcation aneurysm and assess its value for training in endovascular techniques and testing new embolic agents. The experimental aneurysm described herein mirrors human bifurcation aneurysms, and with this model, we sought to reproduce endovascular technical difficulties. However, the lesions created in this canine model did not show angiographic or histologic evidence of aneurysmal recurrence. We conclude that this model may be useful for training in endovascular techniques, but because of the lack of sufficient aneurysmal recurrence, it is not suitable for evaluating new embolic agents.